2004
DOI: 10.1021/jp049384w
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Study of Chemical Composition Influence on the Acidity of H−MCM-22 Zeolite

Abstract: In this work, the influence of the chemical composition (species and number of trivalent substitution atoms) on the acidity of the isomorphously substituted MCM-22 zeolite was investigated in detail by density functional theory. By calculating the proton affinity and NH 3 adsorption energy, it was found that the acidity of the MCM-22 zeolite decreased with increasing number of trivalent substitution atoms introduced into the zeolite framework. Moreover, the acidity of the substituted MCM-22 increased in the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…A number of experimental and theoretical efforts have devoted to clarifying the acidities of M 3+ -doped zeolites [4][5][6][7][8][9][10]. Calculations of various cluster models and theoretical levels indicated that the Brönsted acidities increase in the order B < Fe < Ga < Al-doped zeolites [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of experimental and theoretical efforts have devoted to clarifying the acidities of M 3+ -doped zeolites [4][5][6][7][8][9][10]. Calculations of various cluster models and theoretical levels indicated that the Brönsted acidities increase in the order B < Fe < Ga < Al-doped zeolites [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Calculations of various cluster models and theoretical levels indicated that the Brönsted acidities increase in the order B < Fe < Ga < Al-doped zeolites [7][8][9][10]. Instead, the studies with incorporation of tetravalent ions (M 4+ ) lag far behind [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18][19][20][21][22][23][24][25][26][27] Recently, the Al locations in MCM-22 zeolite were studied by Corma et al and our group. [28][29][30] It was found that these ions are not equally distributed among the various T sites. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Herein, density functional calculations were employed to determine the Ti IV distribution in MCM-22 zeolite.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30] It was found that these ions are not equally distributed among the various T sites. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Herein, density functional calculations were employed to determine the Ti IV distribution in MCM-22 zeolite. The design of isolated titanium dioxide (TiO 2 ) within zeolites is currently a research focus, [31] owing to the unique photocatalytic reactivity of the Ti III sites for a variety Abstract: Isolated Ti species in zeolites show unique catalytic activities for a variety of chemical reactions.…”
Section: Introductionmentioning
confidence: 99%